ANALISIS SISTEM TRANSPORTASI DALAM KAMPUS UNIVERSITAS TADULAKO - Ismadarni, Ismadarni; Pradani, Novita (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2017)
Tadulako  University  as one of  the state  universities  in the province  of  Central  Sulawesi  has  experienced rapid  development.    Physical  growth  that  continues  to  grow  along  with  its  academic  development causes  the movement of traffics activity to participate in the increase. This can cause negative impacts such as high pollution levels, vehicle density and high accident rates often occur in the campus area. This  study aims  to analyze  the  transportation system within the Tadulako University Campus. It is expected that with this research it can be obtained the description of  traffic  problems  that  occurred  in  the campus of Tadulako University includes network system and  road geometry, parking  and  analyzing the  policies  of  traffic  that  is  currently applied  in  the  campus of Tadulako University. Traffic surveys show that motorcycle users account for 66.8% and automobiles 33.2%. Geometric survey shows that the road in the campus  is  relatively good because almost all  roads have been  structured with asphalt with one way road  system. Survey on parking location also indicate that arrangement of parking space at some faculty are required so that vehicle not parked at road body. Further research is necessary to calculate the need for parking space.